2001
DOI: 10.1021/bi010916y
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a Fibronectin Type III Domain by the Removal of Unfavorable Electrostatic Interactions on the Protein Surface

Abstract: It is generally considered that electrostatic interactions on the protein surface, such as ion pairs, contribute little to protein stability, although they may play important roles in conformational specificity. We found that the tenth fibronectin type III domain of human fibronectin (FNfn10) is more stable at acidic pH than neutral pH, with an apparent midpoint of transition near pH 4. Determination of pK(a)'s for all the side chain carboxyl groups of Asp and Glu residues revealed that Asp 23 and Glu 9 have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 37 publications
4
93
1
Order By: Relevance
“…However, Cota et al (2000) demonstrated that mutation of Pro5 to alanine does not effect stability, as would be expected if it does not contribute to the hydrophobic core of 10FnIII alone. Also, Asp7 makes unfavorable electrostatic interactions with other negatively charged residues on the surface of 10FnIII (Koide et al 2001), further validating the removal of the unstructured residues.…”
Section: Discussionmentioning
confidence: 75%
“…However, Cota et al (2000) demonstrated that mutation of Pro5 to alanine does not effect stability, as would be expected if it does not contribute to the hydrophobic core of 10FnIII alone. Also, Asp7 makes unfavorable electrostatic interactions with other negatively charged residues on the surface of 10FnIII (Koide et al 2001), further validating the removal of the unstructured residues.…”
Section: Discussionmentioning
confidence: 75%
“…A synthetic DNA fragment that encodes signal sequence of DsbA (17) was fused to the gene for the template, and the fusion gene was cloned into the phage display vector pAS38 (9). A stabilizing mutation (D7K) was also introduced (18).…”
Section: Methodsmentioning
confidence: 99%
“…The phage display vectors contained the DsbA signal sequence (31), the circularly permutated Erbin PDZ domain, and the FN3 domain (22), in which the PDZ and FN3 domains were connected with a GGSGG linker. A stabilization mutation, D7N (32), was also introduced to FN3. Combinatorial libraries in which the BC, DE, and FG loops of FN3 were diversified were constructed by using Kunkel mutagenesis as previously described (22,33,34).…”
Section: Construction Of Phage Display Vectors and Combinatorial Librmentioning
confidence: 99%